The impact of distance from transplant unit on outcomes following kidney transplantation. (October 2017) - Powell-Chandler, Anna; Khalid, Usman; Horvath, Szabolcs; Ilham, Mohamed A.; Asderakis, Argiris; Stephens, Michael R.
Abstract: Background: Following transplantation, many patients travel long distances for follow-up care. Many studies have examined the influence of distance from transplant centre on access to transplantation, but few have examined post-transplant outcomes. Materials and Methods: Distance from transplant centre was calculated for all kidney transplant recipients transplanted over a 5-year period. Outcomes measured were rates of acute rejection, graft and patient survival. Results: Complete follow up data was available for 571 of the 585 kidney transplants performed over the study period. Distance from home to transplant centre ranged from 1.3 to 257.4 km (median 33.7 km). Patients were divided into quartiles according to their distance from the transplant centre. Distance from the transplant centre did not influence rates of acute rejection (p = 0.102). One-year graft survival for 'nearest' and 'farthest' quartiles was 99% and 97% respectively and five-year graft survival was 78% and 89% respectively (log rank p-value of 0.212). There were no differences in patient survival at 1 and 5 years between the 'nearest' and 'farthest' groups. Conclusion: Distance from transplant centre does not affect early outcomes following kidney transplantation. The centralized practice which involves a low threshold for rapid assessment and readmission of patients post-transplantation appears to provide good outcomes for kidney transplant recipients. Highlights: Impact of distance between home and transplant unit is considered. Distance does not affect acute rejection or renal graft survival. Distance does not affect patient survival after transplant.